2014
DOI: 10.4172/2157-7420.1000143
|View full text |Cite
|
Sign up to set email alerts
|

Human Embryonic Behavior Observed with Time-Lapse Cinematography

Abstract: To clarify developmental behavior in human embryos, we observed oocytes with in vitro fertilization and intracytoplasmic sperm injection and donated embryos up to 5 days using our original time-lapse cinematography (TLC) system. The TLC analyses demonstrated several novel aspects and events that were not visible by intermittent stillframe microscopy. Here, we present the entire fertilization process in which we founded the fertilization cone, cytoplasmic flare, dynamic change of nuclear precursor body and cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Dynamic analyses of TLC images demonstrated several aberrant zygotes with 1PN and uneven 2PN [7]. A previous study has reported that a third PB-like material was extruded into the perivitelline space in some zygotes with 1PN and in uneven 2PN zygotes [7]. Surprisingly, an fPN-like body formed within the third PB-like material in uneven 2PN zygotes and was reabsorbed into the cytoplasm.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…Dynamic analyses of TLC images demonstrated several aberrant zygotes with 1PN and uneven 2PN [7]. A previous study has reported that a third PB-like material was extruded into the perivitelline space in some zygotes with 1PN and in uneven 2PN zygotes [7]. Surprisingly, an fPN-like body formed within the third PB-like material in uneven 2PN zygotes and was reabsorbed into the cytoplasm.…”
Section: Discussionmentioning
confidence: 80%
“…A review of chromosome abnormalities in human embryos after c-IVF and ICSI identified numerous reports that used fluorescence in situ hybridization to study chromosomal status [14][15][16][17][18]. More recently, we developed an in vitro culture system for TLC to analyze human embryonic development from fertilization to the hatched blastocyst stage [7,8,[19][20][21]. Dynamic analyses of TLC images demonstrated several aberrant zygotes with 1PN and uneven 2PN [7].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1) [14,15]. Using this system, we have demonstrated various novel phenomena during embryonic development in human embryos from the fertilization process to the hatched blastocyst stage without any damage to the embryos [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%